2020
DOI: 10.1371/journal.pntd.0008538
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for the role of non-human primates as reservoir hosts for human schistosomiasis

Abstract: Background Schistosomiasis is a chronic parasitic disease, that affects over 207 million people and causes over 200,000 deaths annually, mainly in sub-Saharan Africa. Although many health measures have been carried out to limit parasite transmission, significant numbers of nonhuman primates such as Chlorocebus aethiops (Ch. aethiops) (vervet) and Papio anubis (baboon) are infected with S. mansoni, notably in Ethiopia, where they are expected to have potentially significant implications for transmission and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
13
1
Order By: Relevance
“…One interesting outcome that differsbetween these two studies is that parasite genetic diversity increases only with male or female age Kebede et al (2020) or Faust et al (2019), respectively. This confirms that human behaviour can shape the parasite genetic composition but also,that acquired immunity does not seem to limit this diversity because no decline in genetic diversity was observed (Faust et al, 2019).…”
Section: The Effect Of Host Sex On Parasite Genetic Diversitymentioning
confidence: 93%
See 1 more Smart Citation
“…One interesting outcome that differsbetween these two studies is that parasite genetic diversity increases only with male or female age Kebede et al (2020) or Faust et al (2019), respectively. This confirms that human behaviour can shape the parasite genetic composition but also,that acquired immunity does not seem to limit this diversity because no decline in genetic diversity was observed (Faust et al, 2019).…”
Section: The Effect Of Host Sex On Parasite Genetic Diversitymentioning
confidence: 93%
“…haematobiumfrom infected humans (Gower et al, 2011;Thiele et al, 2008;Van den Broeck et al, 2014). However, two recent studies showed that males have a higher schistosome genetic diversity than females (Faust et al, 2019;Kebede et al, 2020). This could reflect the differences in behaviour with young males having higher mobility and greater water contact compared to young females.…”
Section: The Effect Of Host Sex On Parasite Genetic Diversitymentioning
confidence: 99%
“…As novel human pathogens take hold in human populations there is a need to better understand the transmission routes and factors involved in anthropozoonoses that could endanger other species—an essential process for the creation of procedures and guidelines that will protect NHPs. Importantly, spillover events may also have future consequences since NHPs represent a potential deadly zoonotic reservoir for a variety of human pathogens (Devaux et al, 2019 ; Kebede et al, 2020 ). Therefore, the reduction of inter‐species transmission promotes a healthier community for both NHPs and humans.…”
Section: Commentarymentioning
confidence: 99%
“…However, the definitive host is generally only humans except in schistosomiasis japonica and schistosomiasis mekongi that, in contrast to all other species, are zoonotic forms of the infection. S. mansoni infects sometimes also non-human primates (Kebede et al, 2020) and various rodent species (Gentile et al, 2011).…”
Section: Introductionmentioning
confidence: 99%